Application effect of BOPPPS teaching model on fundamentals of nursing education: a meta-analysis of randomized controlled studies - Li, Yue; Li, Xiao; Liu, Yan; Li, Yang (Frontiers in Medicine, 2024)
Background BOPPPS (bridge-in, learning objective, pretest, participatory learning, posttest, and summary) is a student-centered, closed-loop teaching model that emphasizes real-time communication and feedback. Objectives The purpose of this study was to review and evaluate the effect of BOPPPS teaching model in “Fundamentals of Nursing” teaching. Methods We conducted a meta-analysis of randomized controlled trials (RCTs) based on the BOPPPS teaching model in “Fundamentals of Nursing” teaching. To review domestic and foreign databases for the period 2010 to September 2023. Finally, 13 RCTs were included and the teaching outcomes were measured and analyzed. Two researchers independently identified, selected, and extracted data from the study and examined the risk of bias. The primary outcomes were students’ examination scores (theoretical scores: scores obtained in the nursing fundamentals course, reflecting students’ understanding and mastery of the course content; practical scores: assessment results based on practical application or experimental skills, evaluating students’ practical skill level). The secondary outcomes were self-learning ability score: indicators assessing students’ self-directed learning ability, reflecting their competence in independent learning and autonomous exploration; and satisfaction rate of teaching effect: the overall satisfaction rate of students with the teaching effects experienced during teaching process reflects the proportion of students’ acceptance and satisfaction with the teaching program. The results were evaluated using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) profiler software. The GRADE profiler software is used to assess and grade the recommendations according to the GRADE (Grading of Recommendations Assessment, Development, and Assessment) criteria. Results A total of 13 studies were included, consisting of 2,991 nursing students. Among them, 1,465 students were in the BOPPPS teaching group, while 1,526 students were in the traditional teaching group. The summary analysis of the main outcomes showed that the BOPPPS teaching model had significantly higher scores in theoretical score (MD = 3.35, 95% CI: 2.35–4.35, Z = 6.56, p < 0.00001), practice score (MD = 4.50, 95% CI: 1.95–7.05, Z = 3.45, p = 0.0006), and self-learning ability score (MD = 6.76, 95% CI: 5.38–8.14, Z = 9.60, p < 0.00001) compared to the traditional teaching group. The satisfaction rate of students in the BOPPPS teaching group regarding teaching effectiveness was 89% (95% CI = 0.84–0.93). The differences were statistically significant (p < 0.05). The GRADE evidence level for theoretical score and satisfaction rate of teaching effect is low. The evidence level for practice score is very low, and for self-learning ability score is moderate. Conclusion The BOPPPS teaching mode is helpful to improve the theoretical score, practice score, and self-learning ability score of “Fundamentals of Nursing,” and improve the satisfaction rate of students to the teaching effect. The teaching effect is better than the traditional teaching method.